2020
DOI: 10.1186/s12967-020-02642-z
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory microbiome profiles differ by recent hospitalization and nursing home residence in patients on mechanical ventilation

Abstract: Background Healthcare-associated pneumonia (HCAP) is a heterogeneous disease. We redefined nursing-home- and hospital-associated infections (NHAI) group by revising existing HCAP risk factors. The NHAI group comprised nursing home residents with a poor functional status, or recent (past 90 days) hospitalization or recent (past 180 days) antibiotic therapy. Our aim was to determine whether respiratory microbiota profiles are related to newly defined NHAI group in critically ill patients on mecha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Our data showed that Corynebacterium species were the second most frequently detected bacterial species in patients with HAP (Table 2) and significantly frequently detected in patients with cerebrovascular diseases (Table 3). Corynebacteria usually cause pneumonia in elderly patients with impaired airway clearance and immunocompromised conditions [21]. Patients with cerebrovascular diseases were compatible with these clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that Corynebacterium species were the second most frequently detected bacterial species in patients with HAP (Table 2) and significantly frequently detected in patients with cerebrovascular diseases (Table 3). Corynebacteria usually cause pneumonia in elderly patients with impaired airway clearance and immunocompromised conditions [21]. Patients with cerebrovascular diseases were compatible with these clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they demonstrated that ARDS had abundant Betaproteobacteria, Staphylococcus , Streptococcus , and Enterobacteriaceae, which may play a pivotal role in the pathophysiology of ARDS patients [ 13 ]. Patients who had nursing-home and hospital-associated infection (NHAI) pneumonia had significantly more reduced alpha diversity than non-NHAI pneumonia patients [ 15 ]. Cigarette smoking trauma patients are more likely to suffer from an ARDS.…”
Section: Resultsmentioning
confidence: 99%
“…The individual’s lifestyle and comorbidities also appear to be relevant factors in the composition of an individual microbiome. For example, age influences the composition of the microbiome during pneumonia; thus, elderly patients suffering from nursing-home- or hospital-acquired infection also appear to have reduced alpha diversity [ 15 ]. Patients older than 75 years have a significantly higher number of Streptococcus phylotypes than those aged 74 years and younger [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the evaluated richness and diversity of the lung microbiome may suggest an imbalanced lung milieu. The extent of the similarity between microbial communities based on the degree of structural overlap was characterized by beta diversity (inter-sample diversity) [ 33 ]. The repeatability of samples in each group was determined to be good based on PCoA analysis, and the difference between lung samples was significant.…”
Section: Discussionmentioning
confidence: 99%